Synthesis, binding and self-assembly properties of a well-defined pillar[5]arene end functionalised polydimethylacrylamide. Issue 42 (11th September 2015) - Laggoune, N.; Delattre, F.; Lyskawa, J.; Stoffelbach, F.; Guigner, J. M.; Ruellan, S.; Cooke, G.; Woisel, P.
Abstract : The synthesis, binding and self-assembly properties of a well-defined pillar[5]arene end functionalised polydimethylacrylamide are reported. Abstract : The synthesis, binding and self-assembly properties of a well-defined pillar[5]arene end-functionalised poly(dimethylacrylamide)(MePilla-PDMAC ) are reported. In order to synthesiseMePilla-PDMAC, a new trithiocarbonate type RAFT agentMePilla-CTA was developed incorporting a partially methylated pillar[5]arene moiety. Kinetic studies clearly indicated the propensity ofMePilla-CTA to control the polymerisation of DMAC. Interestingly, as PDMAC type chains display good solubilty both in organic and aqueous media, MePilla-PDMAC was able of specifically bind electron deficient guest molecules at the α-chain-end both in chloroform and water. Complex formation was found to be reversible upon addition of chloride anions or heating in organic and aqueous media, respectively. Furthermore, cryo-TEM, VT-NMR ( 1 H) and VT-DLS investigations also indicated the ability ofMePilla-PDMAC to self-assemble into micelle-like aggregates in water showing reversible recognition properties.